1979
DOI: 10.1111/j.1471-4159.1979.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

A Thiol Proteinase Highly Elevated in and Around the Plaques of Multiple Sclerosis

Abstract: Abstract— A thiol dependent proteolytic enzyme (tentatively identified as carboxypeptidase B) which liberates phenylalanine from CBZ‐glutamyl‐phenylalanine at pH 5.3 was shown, by a sensitive micromethod, to be greatly increased in activity in and around MS plaques. These increases exceeded those of other hydrolases previously measured. Plaque tissue, on the basis of lipid‐free dry weight, is up to 3‐fold richer in this enzyme than control white matter, and most samples of apparently uninvolved MS white matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…6, where the plaques were highly cellular and evidently of recent origin by histological criteria, as they contained mononuclear infiltrates, macrophages, gitter cells, and reactive astrocytes. A similar reduction in the plaques of patients 1, 3, and 5 has previously been documented for acid lipaseesterase (Hirsch and Parks, 1979); in patient 6 this enzyme also parallels GPDH, showing only an 11% reduction in plaque no. 2 (Hirsch and Parks, unpublished experiments).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…6, where the plaques were highly cellular and evidently of recent origin by histological criteria, as they contained mononuclear infiltrates, macrophages, gitter cells, and reactive astrocytes. A similar reduction in the plaques of patients 1, 3, and 5 has previously been documented for acid lipaseesterase (Hirsch and Parks, 1979); in patient 6 this enzyme also parallels GPDH, showing only an 11% reduction in plaque no. 2 (Hirsch and Parks, unpublished experiments).…”
Section: Resultssupporting
confidence: 81%
“…The low activities of these two enzymes and that of the m y e l i n -s p e c i f i c 2 ' -3 ' -c y c l i c n u c l e o t i d e 3 'phosphodiesterase (CNP-ase) (Roytta et al, 1976) in older plaques contrast with those of other enzymes so far measured in these lesions, e.g., lactic dehydrogenase, glucose-6-phosphate dehydrogenase, and various acid hydrolases, all of which are either unchanged or elevated (Hirsch et al, 1976;Hirsch and Parks, 1979). Since oligodendrocytes as well as their myelin disappear from MS plaques and older plaques consist largely of fibrous astrocytes and axons (Adams, 1977), a localization in oligodendrocytes or myelin can be inferred for these en- Values are given as mol per kg lipid-free dry weight per hour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported recently that a decrease in the myelin-associated glycoprotein (MAG) precedes that of BP (Itoyama et al, 1980). In a study of macroscopically normal white matter in MS, a high proportion of samples was found to be histologically abnormal (Allen and McKeown, 1979), and raised activities of several lysosomal hydrolases have been demonstrated in histologically and histochemically normal white matter (Einstein et al, 1972; Arstila et al, 1973;Hirsch and Parks, 1979; Allen and McKeown, 1979). The separation of sodium dodecylsulphate (SDS)-solubilized brain particulate fractions by polyacrylamide gel electrophoresis (PAGE) revealed changes in a number of protein bands in normal-appearing MS white matter, as well as in plaques (Newcombe et al,1 9 8 0~) .…”
mentioning
confidence: 99%
“…Bowen and Davison (1974) argued that the elevated cathepsin A, which is 30-fold more active in macrophages than in brain tissue, was an indicator of the infiltrating phagocytes. Other investigators have concluded that many of the enzymes, especially acid phosphatase, acid proteinase, carboxypeptidase B, and N-acetyl-ß-glucosaminidase, are derived from reactive astrocytes (Cuzner el al., 1976;Hirsch el al., 1976;Hirsch and Parks, 1979;McKeown and Allen, 1978;Allen el al., 1979;Hirsch, 1980Hirsch, , 1981.…”
Section: A Plaquesmentioning
confidence: 99%